Iridium in Tungsten Trioxide Matrix as an Efficient Bi‐Functional Electrocatalyst for Overall Water Splitting in Acidic Media. Issue 45 (5th October 2021) - Li, Pengsong; Duan, Xinxuan; Kuang, Yun; Sun, Xiaoming
Abstract: Electrocatalytic water splitting in acidic media is a promising strategy for grid scale production of hydrogen using renewable energy, but challenges still exist in the development of advanced catalysts with both high activity and stability. Herein, it is reported that iridium doped tungsten trioxide (Ir‐doped WO3 ) with arrayed structure and confined Ir sites is an efficient and durable bi‐functional catalyst for overall acidic water splitting. A low overpotential (258 mV) is required to achieve an oxygen evolution reaction current density of 10 mA cm −2 in 0.5 m H2 SO4 solution. Meanwhile, Ir‐doped WO3 processes a similar intrinsic activity to Pt/C toward hydrogen evolution reaction. Overall water splitting using the bi‐functional Ir‐doped WO3 catalyst shows low cell voltages of 1.56 and 1.68 V to drive the current densities of 10 and 100 mA cm −2, respectively, with only 16 mV decay observed after 60 h continuous electrolysis under the current density of 100 mA cm −2 . Structural analysis and density functional theory calculation indicate that the adjusted coordination environment of Ir within the crystalline matrix of WO3 contributes to the high activity and durability. Abstract : Efficient and durable catalysts are highly desired in the electrolysis of acidic water for hydrogen energy. Iridium (Ir) atoms are successfully doped into hexagonal WO3 crystalline matrix array on carbon fiber paper. The Ir active site with unsaturated coordination exhibits superior OER/HER bi‐functional performance, which shows great potential in acidic water splitting with high current density (100 mA cm −2 ).